2011
DOI: 10.1111/j.1365-2648.2011.05845.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ use of online health information in medical wards

Abstract: The findings of this study highlight that while online resources add to education opportunities, the ongoing nursing assessment required to determine online information needs is not always incorporated into nursing practice. Patient misunderstandings of online material were also identified; developing patient competency in evaluating open access health information should now be recognized as an integral aspect of illness management education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 23 publications
5
53
0
1
Order By: Relevance
“…There was a significant association between assessing patients use and awareness of patient misconceptions. The conclusions of the Gilmour et al [2] study was that the findings highlight that while online resources add to education opportunities, the ongoing nursing assessment required to determine online information needs is not always incorporated into nursing practice. Patient misunderstandings of online material were also identified and it must be admitted that assessing the patients' understanding of as well as the relevance of the information which patients' retrieved from Internet is time consuming in the current setting of busy wards where the patient turnover is rapid.…”
Section: Nursing Students Using the Internetmentioning
confidence: 97%
See 3 more Smart Citations
“…There was a significant association between assessing patients use and awareness of patient misconceptions. The conclusions of the Gilmour et al [2] study was that the findings highlight that while online resources add to education opportunities, the ongoing nursing assessment required to determine online information needs is not always incorporated into nursing practice. Patient misunderstandings of online material were also identified and it must be admitted that assessing the patients' understanding of as well as the relevance of the information which patients' retrieved from Internet is time consuming in the current setting of busy wards where the patient turnover is rapid.…”
Section: Nursing Students Using the Internetmentioning
confidence: 97%
“…Gilmour et al [2] found that online health information is commonly used by patients with chronic illness to support their education needs. Nurses have a critical role in assisting patients to access and use this information.…”
Section: Nursing Students Using the Internetmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas patients may feel justified in stating their difficulties it may not be quite so easy for staff to voice concerns over the use of such tools for fear of criticism and lack of motivation for a Page 13 of 37 14 new potentially valuable aid to clinical care. Some evidence suggests that staff were aware (50%) that service users do check information about their condition and status on the internet but failed to check (24% only) whether the patient consulted online information [49]. 4.…”
Section: Staff Trainingmentioning
confidence: 99%